Gout and Nucleotide Catabolism: A TBL Integrating Basic Science and Clinical Practice - Ralph L. Keil; Barbara E. Ostrov (MedEdPORTAL, 2011)
Abstract Gout is a common disease encountered in medical practice. This team-based learning (TBL) session integrates presentation of clinical aspects of gout with the basic science of nucleotide catabolism and is well suited to the first-year medical student curriculum. Learning involves preclass reading by students, in-class analysis and discussion of clinical scenarios, and interaction with volunteer patients. Assessment of student learning includes an in-class quiz and class discussion. Materials include (1) an introduction of TBL to students, (2) the preclass readings, (3) all materials related to presentation of in-class cases, and (4) an evaluation form for the TBL. This session works well with up to about 75 students organized in groups of about five students each. This TBL session is highly effective and has been well received by students. More than 98% of students (141 out of 144) recommended retaining this session in the curriculum. In fact, when asked to list the least useful aspect of the session, comments such as “I enjoyed it all. I would really hope that more TBL exercises are included into the curriculum” and “Actually none, it was 120% useful, relevant and well done” were received. Inclusion of volunteer patients enhances the effectiveness of this TBL as students hear about real-world experiences with the symptoms and treatments of gout and are able to examine the patients. The first-year medical students who were the target audience of this session enjoyed the incorporation of this clinical relevance into their basic science education. This session was highly evaluated even as the only TBL session in the first-year curriculum.